1997
DOI: 10.1088/0741-3335/39/5a/038
|View full text |Cite
|
Sign up to set email alerts
|

Low-field helicon discharges

Abstract: Abstract. Operation of helicon discharges at magnetic fields B 0 below 100 G is of interest for plasma etching and deposition reactors if high ion flux can be maintained with reduced field requirements. The theory of coupled helicon and Trivelpiece-Gould modes is summarized for uniform B 0 . Initial results from two experiments are reported. The first has a single 5 cm diameter tube with B 0 = 0-100 G injecting plasma into a field-free region. The second contains a two-dimensional array of seven such tubes cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 5 publications
(4 reference statements)
3
26
0
Order By: Relevance
“…In addition, the position of the low-field peak is shifted to lower magnetic field strengths for lower pressure: for example for deuterium the low-field peak position is located at around 4 mT at 1 Pa, at 3.5 mT for 0.5 Pa and at 2.5 mT at 0.3 Pa. This behavior has also been observed in rare gas Helicon discharges [7] but the reason for it is still unclear as well.…”
Section: Behavior Of the Low-field Peakmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, the position of the low-field peak is shifted to lower magnetic field strengths for lower pressure: for example for deuterium the low-field peak position is located at around 4 mT at 1 Pa, at 3.5 mT for 0.5 Pa and at 2.5 mT at 0.3 Pa. This behavior has also been observed in rare gas Helicon discharges [7] but the reason for it is still unclear as well.…”
Section: Behavior Of the Low-field Peakmentioning
confidence: 72%
“…The concept is generally known to produce rare gas discharges with very high efficiency [5,6]. Another prominent feature is the enhancement of the coupling efficiency at a few mT external magnetic field strength, the so-called low-field peak [7], which could be enough improvement regarding the application at ion sources. For the utilization of Helicon coupling, the basic geometry of the ion sources has not to be altered, as both the driver in ion sources for fusion and the discharge vessel at ion sources for accelerators are cylindrical; only an additional magnetic field and a differently shaped antenna have to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…A standard ICP antenna can be exchanged by a helicon antenna (Nagoya type III) which favors together with an axial magnetic field the |m| = 1 helicon mode for propagation. Instead of aiming to operate in the full helicon mode for which several 100 mT are required, the investigations are focussed to achieve the better coupling due to the so-called low-field peak [19]. It has already been demonstrated that the low-field peak appears below 10 mT in hydrogen and deuterium plasmas at the relevant source pressure, showing that in the peak a higher dissociation degrees and plasma densities are achieved [20].…”
Section: Randd On Innovative Ion Sourcesmentioning
confidence: 99%
“…A second RF generator serves for substrate biasing. The substrate was 600 400 mm Chen et al have described a large array of helicon sources [65].…”
Section: A Radial Profilesmentioning
confidence: 99%